Factors affecting the use of patient survey data for quality improvement in the Veterans Health Administration. - Davies, Elizabeth A; Meterko, Mark M; Charns, Martin P; Seibert, Marjorie E Nealon; Cleary, Paul D (BMC health services research, 2011)
Little is known about how to use patient feedback to improve experiences of health care. The Veterans Health Administration (VA) conducts regular patient surveys that have indicated improved care experiences over the past decade. The goal of this study was to assess factors that were barriers to, or promoters of, efforts to improve care experiences in VA facilities.